Encounter as a dimension of cultures and the road to peace - Sosa, Arturo (Razón y fe, 2022)
The structural injustice that characterizes current socio-political relations is a heavy legacy that the historical epoch that has just ended leaves to the new one that is beginning. Indeed, in this changing era we are witnessing situations, such as the Covid-19 pandemic, which, by affecting the whole of humanity, clearly reveal the scope and depth of this structural injustice. Social gaps, poverty, forced migration and other calamities continue to grow. It seems impossible to stop the environmental degradation caused by the lavish production models and lifestyles that globalized consumer capitalism has generated. Armed conflicts continue and increase, even in places where it seemed that alternatives to resolve conflicts had been found. World politics has proven to be immature, incapable of governing the world in the common interest of humanity. Against this backdrop, we need intercultural encounter as a path to peace.